Tracking Short-Term Dynamics of Economic Activity in Low-Income Countries in the Absence of High-Frequency Gdp Data - Dixit, S. V. S. (IMF Working Papers; Working Paper, 2012)
This paper uses a set of routinely collected high-frequency data in low-income countries (LICs) to construct an aggregate and a comprehensive index of economic activity which could serve (i) as a measure of the direction of economic activity; and (ii) as a useful input in analyzing contemporaneous real sector performance in LICs in the absence of high-frequency, and often outdated, GDP data. It could also serve as a useful tool for policymakers to gauge short-term dynamics of economic activity and shape appropriate and timely policy responses.